The Efficiency of Islamic Banks in North Africa: Analysis with the Non-Parametric Approach DEA (Window Analysis) (Global Journal of Management and Business Research, 2016)
Abstract not found
Keywords: islamic banks; north africa; efficiency; financial ratios; the method DEA